2022
DOI: 10.1039/d2an00517d
|View full text |Cite
|
Sign up to set email alerts
|

A multicolor biosensor for alkaline phosphatase activity detection based on the peroxidase activity of copper nanoclusters and etching of gold nanorods

Abstract: A multicolor biosensor for ALP activity has been developed based on the peroxidase activity of copper nanoclusters and etching of gold nanorods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The target can keep the shape of the LSPR unchanged by hindering the etching of Au NPs and the etching rate can be varied by controlling the concentration of the inhibitor under specific conditions. Luo et al developed a multicolor biosensor for ALP activity detection based on the peroxidase-like activity of Cu NCs and the etching of Au NRs [ 119 ]. Cu NCs could catalyze the oxidation of TMB to generate TMB 2+ , which in turn etched Au NRs, and the etching process was accompanied by a significant change in the color of the system.…”
Section: Sensing Strategy Based On the Lspr Properties Of Au Npsmentioning
confidence: 99%
“…The target can keep the shape of the LSPR unchanged by hindering the etching of Au NPs and the etching rate can be varied by controlling the concentration of the inhibitor under specific conditions. Luo et al developed a multicolor biosensor for ALP activity detection based on the peroxidase-like activity of Cu NCs and the etching of Au NRs [ 119 ]. Cu NCs could catalyze the oxidation of TMB to generate TMB 2+ , which in turn etched Au NRs, and the etching process was accompanied by a significant change in the color of the system.…”
Section: Sensing Strategy Based On the Lspr Properties Of Au Npsmentioning
confidence: 99%
“…In recent years, the application and research of noble metal nanomaterials have opened a new development path for colorimetric biosensors. It is well known that gold nanorods (Au NRs) are a good chromogenic agent for visualization sensors and have been applied to design many visualization sensors with excellent performance. , For example, Ma et al revealed that the ultimate yellow product (TMB 2+ ) of the horseradish peroxidase (HRP)-TMB catalytic system is able to quantitatively etch Au NRs, resulting in a significant color change. In this study, once the immunocomplex is formed, the HRP bound to the ELISA plate oxidizes TMB into TMB + , and TMB + is oxidized to TMB 2+ under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%